Drama-Based Pedagogy to Improving Students' Fluency: Classroom Action Research - Yudiarta, Gede Raditya Stava; Suwastini, Ni Komang Arie; Mahayanti, Ni Wayan Surya (English Education Department STKIP Agama Hindu Singaraja, 2025)
Using Drama-Based Pedagogy and CAR, this study aims to improve students' speaking fluency. The study was conducted at SMPN 5 Singaraja, with 35 students in grade IX. As a result of limited exposure to English communication and a lack of self-confidence, initial observations revealed that students struggled to speak fluently. To address this issue, the researcher employed a drama-based teaching approach that incorporates activities such as role-playing, expressive reading, and dramatization. This approach involves stages of engagement, activation, reflection, and application. The study was conducted in two cycles: planning, action, observation, and reflection. Pre-tests, post-tests, observations, and interviews were used to collect data. The results of the study indicate that students' speaking fluency continued to improve.